PELATIHAN PENGEMBANGAN KUALITAS TENAGA PENDIDIK TINGKAT SEKOLAH DASAR KABUPATEN BEKASI, JAWA BARAT - Indra Pradana Singawinata; Ade Fadli Fachrul; Boy Febrian Fachrul (Universitas Trisakti, 2021)
Teachers as the spearhead of education play a very important role in producing reliable national leaders who can bring the nation towards a better life. Responding to the challenge of improving Indonesian Human Resources so that they can compete in the current era of globalization, efforts should be made to improve the quality of teacher education. The purpose of this activity is to provide teachers with knowledge and skills to increase their teaching abilities; carry out learning activities that can actively involve students; apply appropriate learning strategies so as to develop students' potential optimally; and teachers can reflect on their performance in order to always improve and develop innovation as a professional teacher. The implementation of community service through PT PII (Persero)'s CSR program is carried out with PT Shamara Performa Berdaya (Speed) which is committed to providing full support in the form of the Elementary Level Educator Quality Development Program. This activity was carried out for 1 (one) month from November 20 to December 12 2019, located in 5 (five) Elementary Schools (SD), namely: 1) SDN 01 Bojongmangu; 2) SDN 02 Bojongmangu; 3) SDN 03 Bojongmangu; 4) SDN 01 Medal Krisna and 5) SDN 02 Medal Krisna which is located in the Bekasi Regency area, Bojongmangu District. The results of community service activities through the Elementary School Teacher Quality Development Program provide basic skills and the formation of a new paradigm that is in accordance with the demands of the 21st century so that teachers can improve their skills in leading the classroom and be creative in developing learning activities for their students so that teachers can make changes in their respective schools